PENGEMBANGAN BAHAN AJAR FISIKA SMA BERBASIS LEARNING CYCLE (LC) 3E PADA MATERI POKOK TEORI KINETIK GAS DAN TERMODINAMIKA - Mussani -; Susilawati -; Aos Santosa Hadiwijaya (Jurnal Penelitian Pendidikan IPA, 2015)
This study aims to develop teaching materials based high school physics learning cycle ( LC ) 3E in the subject matter and thermodynamics kinetic theory of gases. The study was conducted using the R & D approach is adapted from Brog and Gall which includes the preliminary study stage, stage of development, and testing phases. At this stage of the analysis of the results of a preliminary study conducted literature studies and field studies so that the resulting formulation needs teaching materials physics. Stage of prototype development was done with the preparation of teaching materials and support tools, expert validation, evaluation and improvement, limited testing, and evaluation and improvement. Phase of testing was conducted at SMAN 5 Mataram which aims to determine the effectiveness of the products teaching materials in improving learning outcomes physics students and determine the feasibility of the product. Tests carried out using an experimental method pretest - posttest control group design involving two classes as the sample that is class XI Science 2 class with 33 students as experiment with new teaching materials and class XI IPA 5 with 32 students as the control class with the old teaching materials. The effectiveness of teaching materials was analyzed using Anacova test at a significance level of 5 %. Anacova obtained from the analysis of  Fcount = 7.54 > Ftable = 4.00 which indicates that the physics - based teaching materials more effective learning cycle to improve student learning outcomes physics. The response of students to the teaching material products obtained through questionnaires and analyzed descriptively. The results of the analysis suggests that both aspects of the content, language, presentation, and graphical obtain responses with an average assessment in the high category, so that the product is fit for use in the teaching of physics in the subject matter kinetic theory of gases and thermodynamics at the high school level. Keywords: Development of teaching materials, learning cycle, the kinetic theory of gases and thermodynamics